N-butyl cyanoacrylate embolization using a detachable tip microcatheter: initial experience. (8th April 2014) - Paramasivam, Srinivasan; Altschul, David; Ortega-Gutiarrez, Santiago; Fifi, Johanna; Berenstein, Alejandro
Abstract : Introduction: Endovascular embolization of intracranial vascular malformations with N-butyl cyanoacrylate (nBCA) using a detachable tip microcatheter allows prolonged injection and decreases the risk of catheter retention. Methods: Between March and December 2013, the Apollo 1.5 cm detachable tip microcatheter was used in five patients after being approved by both the Food and Drug Administration and the institutional review board as a compassionate use device. Nine pedicles were embolized and the follow-up ranged from 1 to 3 months. Results: Five of the nine catheter tips detached. The length of reflux was not directly associated with the detachment of the distal tip. There were no cases of premature microcatheter detachment during navigation, manipulation with multiple microguidewire reintroduction and guidance. There was no leak of embolic agent at the detachment zone. Follow-up showed the detached tip to be stable without migration. Conclusions: A detachable tip microcatheter offers an advance in the safety and effectiveness of nBCA embolization. Catheter retrieval becomes more controlled and less traumatic. Our initial experience is encouraging, and more experience is needed to categorically ascertain its safety and efficacy.